Core‐Shell Structured Bi‐Amorphous SiO2@TiO2 Composite for Lithium‐Ion Batteries Anode Material with Ultra‐Stable Performance. Issue 17 (5th May 2020) - Yao, Yixin; Li, Yao; Li, Cheng; Zhou, Junshuai; Wu, Qibing; Zheng, Yan‐Zhen; Wu, Jiaojiao; Zhou, Zhou; Ding, Haiyang; Tao, Xia
Abstract: Surface coating strategies have shown to be effective for improving the cyclability of SiO2 anode materials of lithium‐ion batteries (LIBs). Herein, we prepared commercially amorphous SiO2 nanoparticles encapsulated in amorphous titanium oxide shells (a‐TiO2 ) (SiO2 @a‐TiO2 ) by a facile hydrolysis of titanium isopropylate in alkaline alcohol system. The elastic a‐TiO2 shell can mitigate the volume change of amorphous SiO2 in the lithiation/delithiation processes and improve the electrical conductivity of SiO2 ‐based anodes. By delicately optimizing the a‐TiO2 shell (12.18 wt.%), SiO2 @a‐TiO2 composite delivers a superior cycling capacity of 647 mA h g −1 at a current density of 0.1 A g −1 after 300 cycles, corresponding to an admirable capacity retention rate of 87.3% from the 2nd to 300th cycle. The SiO2 @a‐TiO2 composite with core‐shell structures has outstanding electrochemical performance, which is prepared by a low‐cost and facile solution approach, thus it is expected to realize the large‐scale production of SiO2 ‐based anode materials. Abstract : Core‐shell structured bi‐amorphous SiO2 @TiO2 composite is prepared by a facile hydrolysis of titanium isopropylate in alkaline alcohol system. The elastic amorphous‐TiO2 shell can mitigate the volume change of amorphous SiO2 in the lithiation/delithiation processes and improve the electrical conductivity of SiO2 ‐based anodes. Thus, the SiO2 @TiO2 composite as anode materials shows excellent cycle performance.